Enrichment of Rice Straw Silage with Sacha Inchi (Plukentia volubilis L) Meal and Sambung Nyawa (Gynura procumbens) Leaves - Azzahra, Fikri Fatimah; Widyastuti, Yantyati; Kumalasari, Nur Rochmah (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
Farmers in Indonesia utilize a substantial amount of rice straw to provide feed for their livestock but restricted in terms of its low nutritional value. This study was conducted with objective to evaluate the quality of rice straw silage with addition of sacha inchi (Plukenetia volubilis L.) meal and sambung nyawa (Gynura procumbens) leaves based on physical, chemical, and microbiological properties. The study employed a completely randomized design with 9 treatments (P0: 100% rice straw, P1: 90% rice straw + 10% sacha inchi meal, P2: 85% rice straw + 15% sacha inchi meal, P3: 80% rice straw + 20% sacha inchi meal, P4: 75% rice straw + 25% sacha inchi meal, P5: P1+10% sambung nyawa leaves, P6: P2+10% sambung nyawa leaves, P7: P3+10% sambung nyawa leaves, P8: P4+10% sambung nyawa leaves) and 5 replications, incorporating the addition of sambung nyawa leaves. The variables examined include the physical quality i.e. colour, flavour, texture, and presence of mold; chemical quality i.e. pH, crude protein (CP), and crude fibre (CF); and microbiological quality i.e. lactic acid bacteria (LAB), yeasts, aerobic bacteria, and pathogenic bacteria. The results of the physical quality test indicated that the addition of sacha inchi meal and sambung nyawa leaves resulted no significant difference. On the other hand, the chemical quality showed that the addition of sacha inchi meal and sambung nyawa leaves have enhanced the rice straw silage nutritional content (p<0.05) particularly CP content by about 4 fold. The microbiological tests showed that the addition of sacha inchi meal and sambung nyawa leaves had an impact on the preservation of silage by inhibiting the growth of pathogenic microorganisms. It is concluded that the quality of rice straw silage has improved by the addition of 10-25% sacha inchi meal and 10% sambung nyawa leaves